Illegal Fishing in Indonesia and the Role of International Maritime Law on Illegal Fishing Action - Hertantyo Rizki Gumilar (Indonesian Journal of Environmental Law and Sustainable Development, 2022)
Indonesia as one of the largest maritime sources face many challenges, one of is illegal fishing. This study aims to analyze the role of international maritime law and its practices on handling illegal fishing in Indonesia. Thisy study found and confirmed that illegal fishing action or action of foreign fishing vessels entering the territorial waters of Indonesia without permits and exploiting the natural wealth in it, would violate the sovereignty of the State of Indonesia. For that there must be a firm law enforcement in the form of catching foreign fishermen and their ships to be processed legally. The capture of foreign fishing vessels may be justified if they are filled with evidence that the fishing vessel is conducting illegal fishing. Associated with the problem of illegal fishing, the effort of a State that suffered losses is also a thing to be reckoned with. Efforts taken by a State in handling cases of illegal fishing must be regulated in a clear regulation. In fact, the efforts taken by a State with a different State.